TINGKAT PENGETAHUAN TERKAIT DAMPAK NEGATIF MEROKOK PADA MAHASISWA POLITEKNIK NEGERI MADURA - Qurnia Andayani; Kholilur Rohman; Kristian Triatmaja Raharja; Taufiqur Rahman (Bajang Institute, 2025)
Introduction: Smoking is very detrimental from an economic point of view, especially for smokers who do not have their own source of income, because they spend a lot of money just to consume it. Due to their resistance to harmful substances, smoking becomes more dangerous for people who are close to smokers, also known as passive smokers, who inhale their cigarette smoke without a filter. Objective: The aim of this study is to determine the knowledge of the dangers of smoking in student at the Madura State Polytechnic. Method: The type of research used in this research was descriptive research using a survey research design. The population in this study were students who smoked at the Madura State Polytechnic. The sampling technique in this study used simple random sampling of 89. This study used one variable, namely a description of the negative impact of smoking on students. This research was carried out on May 4 2024. Data collection in this research was carried out by giving a questionnaire in the form of a g-form, then data processing was carried out in the form of editing, scoring, coding, tabulating and interpreting. Data analysis in this study used descriptive (percentage). Results: The research results show that the majority of respondents have sufficient knowledge about the negative impact of smoking on Madura State Polytechnic students. Conclusion: Knowledge and attitudes can influence smoking habits in teenagers. Cigarettes are very dangerous for teenagers' health because smoking is the same as introducing dangerous substances that have negative effects into the body.